Evaluasi Tata Kelola dan Manajemen Risiko Teknologi Informasi pada PT. IKI Karunia Indonesia menggunakan COBIT 2019 - Millenia Silvianthie; Suprapto Suprapto; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. IKI Karunia Indonesia is a website-based lending company called IKI Modal. PT. IKI Karunia Indonesia is currently officially recognized by the Indonesian Joint Funding Fintech Association and registered with a license from the Financial Services Authority. In accordance with the company's mission where the company seeks to commit to compliance and good management by always utilizing IT, of course this must be balanced with proper IT management. Because if not managed properly, IT related risks will arise and can paralyze the company because most of its business processes are supported by the use of IT. Therefore, this research was conducted to assess the extent to which companies are capable of managing IT risk management using COBIT 2019 through EDM03 and APO12, as well as gap analysis and recommendations for improvement steps to achieve the desired level. The results of this found that the EDM03 and APO12 processes achieved capability level 2 with a gap value in each process of 1. To increase capability level achievements, recommendations given to companies include making risk appetite guidelines, listing risk issues, and making risk scenario based on business lines and functions.